Metabolic Fate of Orally Ingested Proanthocyanidins through the Digestive Tract - Yoshimi Niwano; Hidetsugu Kohzaki; Midori Shirato; Shunichi Shishido; Keisuke Nakamura (MDPI AG, 2022)
Proanthocyanidins (PACs), which are oligomers or polymers of flavan-3ols with potent antioxidative activity, are well known to exert a variety of beneficial health effects. Nonetheless, their bioaccessibility and bioavailability have been poorly assessed. In this review, we focused on the metabolic fate of PACs through the digestive tract. When oligomeric and polymeric PACs are orally ingested, a large portion of the PACs reach the colon, where a small portion is subjected to microbial degradation to phenolic acids and valerolactones, despite the possibility that slight depolymerization of PACs occurs in the stomach and small intestine. Valerolactones, as microbiota-generated catabolites of PACs, may contribute to some of the health benefits of orally ingested PACs. The remaining portion interacts with gut microbiota, resulting in improved microbial diversity and, thereby, contributing to improved health. For instance, an increased amount of beneficial gut bacteria (e.g., Akkermansia muciniphila and butyrate-producing bacteria) could ameliorate host metabolic functions, and a lowered ratio of Firmicutes/Bacteroidetes at the phylum level could mitigate obesity-related metabolic disorders.